Circadian tau differences and rhythm associations in delayed sleep–wake phase disorder and sighted non-24-hour sleep–wake rhythm disorder. Issue 1 (3rd July 2020) - Micic, Gorica; Lovato, Nicole; Ferguson, Sally A; Burgess, Helen J; Lack, Leon
Abstract: Study Objectives: We investigated biological and behavioral rhythm period lengths (i.e. taus ) of delayed sleep–wake phase disorder (DSWPD) and non-24-hour sleep–wake rhythm disorder (N24SWD). Based on circadian phase timing (temperature and dim light melatonin onset), DSWPD participants were dichotomized into a circadian-delayed and a circadian non-delayed group to investigate etiological differences. Methods: Participants with DSWPD ( n = 26, 17 m, age: 21.85 ± 4.97 years), full-sighted N24SWD ( n = 4, 3 m, age: 25.75 ± 4.99 years) and 18 controls (10 m, age: 23.72 ± 5.10 years) participated in an 80-h modified constant routine. An ultradian protocol of 1-h "days" in dim light, controlled conditions alternated 20-min sleep/dark periods with 40-min enforced wakefulness/light. Subjective sleepiness ratings were recorded prior to every sleep/dark opportunity and median reaction time (vigilance) was measured hourly. Obtained sleep (sleep propensity) was derived from 20-min sleep/dark opportunities to quantify hourly objective sleepiness. Hourly core body temperature was recorded, and salivary melatonin assayed to measure endogenous circadian rhythms. Rhythm data were curved using the two-component cosine model. Results: Patients with DSWPD and N24SWD had significantly longer melatonin and temperature taus compared to controls. Circadian non-delayed DSWPD had normally timed temperature and melatonin rhythms but were typically sleeping at relatively late circadian phases compared to those with circadian-delayed DSWPD. Conclusions: People with DSWPD and N24SWD exhibit significantly longer biological circadian rhythm period lengths compared to controls. Approximately half of those diagnosed with DSWPD do not have abnormally delayed circadian rhythm timings suggesting abnormal phase relationship between biological rhythms and behavioral sleep period or potentially conditioned sleep-onset insomnia.